PENGARUH CONTENT YOUTUBE CHANNEL ACEP GATES TERHADAP OPININI SUBSCRIBER TENTANG ODHA - Sitorus, Dori Silviani Br.; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Youtube is a social media platform that provides many kind of video, including video blog content (vlog). Vlog usually done by taking in front of camera, talking about something that we like, sharing some tips, or anythingthat goes our mind. One of the youtube who makes vlogs is Aceep Gates. Acep Gates’ vlog talk about HIV and his experience as PLWHA (People Live With HIV/AIDS), which means Acep Gates hopes his Channel can change the opinion among society and reduce the number of discrimination toward PLWHA. This research used S-R theory with the purpose to analyze wheter there is the effect of content on Acep Gates’ Youtube Channel on subscriber’s opinion toward PLWHA or not. The method used in this study is quantitative explanative with random sampling technique and the number of samples is 400 respondents. Data collection techniques in this study used a questionnaire. To find out the influence between two variables, the author uses simple linear regression analysis. Then the data testing is done with the SPSS program for Windows version 21. Based on the results of simple linear regression, the regression coefficient value obtained in this study is Y = 6.712 = 0.517 X with a significance level of 0.000. The significance level is smaller than α = 0.05, which means that Ho is rejected and Ha is accepted, with the statement there is the effect of Acep Gates’ Youtube Channel content on subscriber’s opinion about PLWHA. The coefficient of determination (R2) in this study amounted to 40,6% which means these figures show that the effect of Acep Gates’ Youtube Channel content on subscriber’s opinion about PLWHA included in the medium category. While the remaining 59.4% is influenced by other variables not included in this study. Keyword: ContentYoutube,HIV/AIDS,ODHA,Opini